Factors Influencing Dividend Policy of UK Listed Companies - Huang, Qi (2009)
This paper investigates the key factors influencing dividend payout policy of UK listed companies on London Stock Exchange from 1998-2007. The focus of this research will be put on cash dividend payout policy. In other words, this paper tries to answer the question ‘what factors could influence the level of cash dividend payouts of UK listed companies between 1998 and 2007?’. Those factors will be taken as inferences for the determinants of UK listed companies’ dividend policy. Fixed effects model is used and six factors are found having significant influences on dividend per share, and hence having influences on the dividend policy of UK listed companies between 1998 and 2007. The six factors are: Firm Size (LNMCAP), financial leverage (DER), asset growth (GROWTH), profitability (EPS), free cash flow per share (FCF), and firm life-cycle (RETA). Of these six factors, Firm size (LNMCAP), financial leverage (DER), profitability (EPS) and firm life-cycle (RETA) are the 4 most significant factors that all have positive impacts on dividend per share, followed by Asset growth (GROWTH) and free cash flow per share (FCF) which both have negative impacts on dividend per share. On the whole, transaction costs of external financing, profitability, firm life-cycle theory and investment opportunities all have significant influences that are consistent with traditional literature on UK listed companies’ dividend policy; whilst agency costs also have significant influence but in the opposite direction as opposed to traditional literature.